The Economic Impact of Hospitality Sector Tax Contributions on Genuine Regional Income: A Case Study of Karo District - Della Puspita Purba; Reza Faujan Zalmi; Rio Pranata Sinaga (Law and Economics, 2024)
The hospitality sector in Karo District, North Sumatra, Indonesia, plays a pivotal role in driving economic growth, creating employment opportunities, and contributing to the genuine regional income. This research aims to analyze the economic impact of hotel and restaurant tax contributions to genuine regional income in Karo District, exploring the implications for economic development, fiscal policy, and community welfare. The research design for this study is primarily exploratory and descriptive, employing a mixed-methods approach combining quantitative analysis of tax revenue data with qualitative insights from interviews, surveys, and case studies. Data will be collected from government sources, including local tax records, financial reports, and economic indicators, supplemented by secondary data sources such as government publications, academic journals, and industry reports. Quantitative analysis will involve statistical methods to identify patterns, trends, and correlations between tax revenues, economic indicators, and regional income. Qualitative analysis will involve thematic analysis of stakeholder perspectives, challenges, and opportunities related to hotel and restaurant taxation. The findings of this research will contribute to the existing literature on the economic impact of hotel and restaurant taxes, providing valuable insights into the role of the hospitality sector in driving economic development and community welfare.